Progressivism in Islamic Religious Education: A Philosophical Framework for Contemporary Pedagogical Transformation - Nurjannah; Sitti Fauziah (Dirasah: Jurnal Pendidikan Islam, 2025)
This study explores the philosophical foundation of progressivism and its relevance to Islamic Religious Education in the modern era. Utilizing a descriptive qualitative method through a philosophical literature review, the research critically analyzes key sources to construct a pedagogical framework that integrates Islamic values with progressive educational principles. The findings reveal that progressivism emphasizes student-centered, experiential learning, flexible curricula, and the teacher’s role as a facilitator. These principles align with Islamic education goals when filtered through monotheistic and ethical values. Despite challenges such as cultural resistance and limited teacher capacity, progressivism offers a transformative approach to IRE by fostering contextual, critical, and democratic learning. The study concludes that progressivism provides a philosophical and practical basis for renewing Islamic Religious Education in the 21st century.